ETHNOMATHEMATICAL EXPLORATION OF THE TRADITIONAL FABRIC OF KARAWO GORONTALO IN RELATION TO THE CONCEPT OF TRANSFORMATION GEOMETRY - Kobandaha, Putri Ekawaty; Arief, Ilham; Ibrahim, Nur Fadillah; A, Wikan Tiyasning (PATTIMURA UNIVERSITY, 2025)
This study aims to explore the ethnomathematics contained in the traditional fabric motifs of Karawo Gorontalo in relation to the concept of geometry transformation. This research is qualitative in ethnographic design. The subjects of this study were Karawo embroidery craftsmen with research locations in Karawo production houses, Ayula village, Tapa district, Bone Bolango regency, Gorontalo Province. Data collection techniques with observation, interviews, documentation studies, and literature studies are then analyzed using Spradley’s domain analysis method. The results showed that is an embroidery art that has been preserved since 1600 AD and continues to be preserved by Gorontalo women until now. Karawo also has a manufacturing process that includes slicing and plucking yarn, Mo-Karawo or embroidery, and the last stage is to make refinement. The Ethnomathematics of Karawo fabric embroidery patterns is the geometry of transformation, which is some motifs that can apply the concepts of translation, reflection, dilation, and rotation. This application shows a relationship and can explain the relationship between the concept of transformation geometry and Karawo and can also be illustrated in the Cartesian diagram.